2018
DOI: 10.1021/acssuschemeng.8b04899
|View full text |Cite
|
Sign up to set email alerts
|

From Rusting to Solar Power Plants: A Successful Nano-Pattering of Stainless Steel 316L for Visible Light-Induced Photoelectrocatalytic Water Splitting

Abstract: A novel propitious nanoporous anodized stainless steel 316L (NASS316L) photoanode was developed for water splitting. The anodization could successfully produce a uniform nanoporous (∼ 90 nm in pore diameter) array (∼ 2.0 μm thick) of NASS316L with a high pore density. Several techniques, including FESEM, EDX, XRD, XPS, ICP-OES, and UV–vis-NIR spectrophotometry, were employed to characterize the catalyst and to assess and interpret its activity toward water splitting. Surprisingly, the NASS316L retained almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…Stainless steel materials have been used in large-scale production in alkaline water electrolysis technologies as they are characterised by high corrosion resistance in this environment that attributed to the spontaneous formation of a thin, adherent, and self-healing passive film on the surface. 22–25 For instance, stainless steel 316L has been deemed as an outstanding current collector as well as electrode substrate for splitting of water in alkaline media. In addition to their use as current collectors, bipolar, or end plates, stainless steel electrodes showed a good catalytic activity for catalyzing the OER in alkaline media.…”
Section: Introductionmentioning
confidence: 99%
“…Stainless steel materials have been used in large-scale production in alkaline water electrolysis technologies as they are characterised by high corrosion resistance in this environment that attributed to the spontaneous formation of a thin, adherent, and self-healing passive film on the surface. 22–25 For instance, stainless steel 316L has been deemed as an outstanding current collector as well as electrode substrate for splitting of water in alkaline media. In addition to their use as current collectors, bipolar, or end plates, stainless steel electrodes showed a good catalytic activity for catalyzing the OER in alkaline media.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that during passivation of stainless steel there is an enrichment of nickel in the metal matrix beneath the oxide layer, as dominantly chromium and iron are oxidized to form the passive layer. 37 On the other hand, it was reported by 12 that in the case of stainless steel anodization in organic electrolytes at high voltages, all components are uniformly dissolved. In our case, XPS depth profile did not give any indication of selective dealloying.…”
Section: Resultsmentioning
confidence: 99%
“…Another method for growing a porous oxide was presented previously, 10,11 in which a squared shaped wave potential was applied in an acidic electrolyte, leading to a dissolution/deposition process to grow a disordered porous oxide film on stainless steel AISI 304 and 316L respectively. Farrag et al 12 also obtained a porous oxide layer in a 316L substrate using an acidic, fluorine containing organic based electrolyte.…”
mentioning
confidence: 99%
“…Nowadays, commercial SS, usually consisting of transition metal elements (eg. Fe, Ni, and Cr), has received extensive attention for the electrochemical study owing to its low-cost, good conductivity and chemical stability, [3][4][5][6][7] especially in the field of electrocatalytic OER. Lots of research results have proved that SS could be converted into cheap, efficient, and stable OER electrodes through specific surface treatments, and the main active ingredient is focused on NiÀ Fe (oxy)hydroxide, which is considered as the highly active species for OER under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%